Flow of plastic material between rotating plates: distinguishing features of the solution - Alexandrov, Sergey Evgen'evich (Computational Continuum Mechanics, 2009)
The flow of rigid perfectly/plastic material between two rotating plates with rough surfaces is considered. An analytic solution to the boundary value problem formulated in this study is obtained by an inverse method under standard assumptions for this class of problems. The main purpose of the present research is to investigate the qualitative behavior of solutions in the vicinity of the line of intersection of two friction surfaces. A comparison between the new solution and other known solutions of boundary value problems, whose formulations also include two intersecting friction surfaces, is made.